Brazilian hospital network uses managerial indicators to manage its units - Claude Machline; Antônio Celso Pasquini (O Mundo da Saúde)
Hospitals work with more indicators than any other segment of economic activities. This paper focuses the case of a Brazilian private hospital network, comprising 45 units, which uses 352 managerial indices and relevant data in order to control monthly its hospitals. An advantage offered by the management of a hospital network is the possibility of compare systematically the performance of the several units, making use of benchmarking in order to emulate the best practices. Samples of the monthly reports utilized by the network are shown. Definitions and comments are presented in the paper on the theme which has not yet received the attention it deserves and still raises many questions.